رمزية المكوّن السّردي في تصوير الصراع مع السّلطة رواية العمى لخوسيه دي سوزا أنموذجا - بلعابد فوزية; مرتاض محمد (University of Eloued جامعة الوادي, 2025)
يهدف البحث إلى دراسة رمزية المكوّن السّردي ودورها في تصوير الصراع مع السلطة من خلال رواية "العمى" ل"خوسيه دي سوزا " الملقّب بـ "ساراماغو"، هذا التفاعل الّذي يعدّ مزيجا من الواقعية القاسية للنفس البشرية حين تتعرّض للمواقف المؤلمة واستفزازات الحكم، وقد صوّرت الرواية ذلك في أحداث متسلسلة على لسان الرّوائي المثقّف ومنظوره للواقع. من خلال قراءة الرواية مضمونا، واستكشاف رمزية المكوّنات السّردية سيميائيا؛ الغلاف، العنوان، اللغة، الشّخصيات، الأحداث، ومن خلال تتبع الترابط الفنّي المضمر بين صراع السّلطة ورمزية ساراماغو، خلصنا إلى أنّ رواية "العمى" تتجاوز الجانب الماتع للسّرد إلى الكلمات النّاقدة التي تكشف أنّ صراع الإنسان مع السّلطة لن ينتهي إلا بشفاء المجتمعات من العمى الذي يصيبها. Abstract: The research aims to study the symbolism of the narrative component and its role in depicting the struggle with power through the novel "Blindness" by "Jose de Souza" nicknamed "Saramago". This interaction is a mixture of harsh realism of the human soul when it is exposed to painful situations and provocations of judgment. The novel is about a series of events on the tongue of the educated novelist and his perspective on reality. We analyze the novel in content, and explore the symbolism of the narrative components semiotically; The cover, the title, the language, the characters, and the events, and by tracing the implicit interrelationship between the power struggle and the symbolism of Saramago.We concluded that the novel "Blindness" goes beyond the funny side of the narrative to the critical words, which reveal that the human struggle with power will not end unless societies heal from the blindness that they suffered from.
The Symbolism Of The Narrative Component In Depicting The Struggle With Power: The Novel "blindness" By "jose De Souza" As A Model
مقال . مجلة العلوم العربية
Keywords: المكوّن السّردي؛ الرّمزية؛ صراع السلطة؛ رواية العمى؛ خوسيه دي سوزا (ساراماغو); narrative component; symbolism; power struggle; blindness novel; Jose de Souza (Saramago).